The Effect of Dhuha Prayer Habituation on the Awareness of Performing Fard Prayers among Madrasah Ibtidaiyah Students - Dedih Surana; Giantomi Muhammad; Iwan Sanusi; Haditsa Qur’ani Nurhakim; Muhamad Imam Pamungkas (Universitas Islam Negeri (UIN) Salatiga, 2024)
This study examines the influence of Duha prayers on students' daily performance of fardhu prayers. A quantitative approach was utilized, involving surveys, questionnaires, and interviews for data collection. Descriptive statistical analysis was conducted. The research findings indicate a correlation between regular Duha prayers and students' adherence to fardhu prayers at home, with a 20.5% and 79.5% difference in performance before and after implementing the Duha prayer, respectively, which can be attributed to various factors. This percentage demonstrates the impact of the habit of Duha prayers on students' consciousness in fulfilling fardhu prayers, with the main contributing factor being the students' awareness developed through consistent practice at school. The consistent practice of habits can significantly influence a person's personality. Similarly, incorporating the habit of performing the Duha prayer is essential in shaping students' personalities. The implementation of fardhu prayers at home has a noticeable impact on students. Since fardhu prayers are obligatory for Muslims, it is essential to have a supportive process to ensure their fulfillment.